2008
DOI: 10.1111/j.1467-9752.2008.00605.x
|View full text |Cite
|
Sign up to set email alerts
|

Troubled Theory in the Debate between Hirst and Carr

Abstract: When Paul Hirst and Wilfred Carr squared up to each other a few years ago on the issue of the role of philosophical theory in educational practice, it became clear that theory itself had become a troubled term. The very fact that Wilfred Carr could argue for the end of educational theory recalls Paul Feyerabend's fiery argument for the end of theory in natural science and simply deepened the attack that had already appeared in Carr and Kemmis's book, Becoming Critical (1986). In response, Hirst insisted that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…However, as Long has shown, theory had different meanings in Aristotle's view, the most comprehensive list of which includes techne , episteme, phronesis , noûs , and sophia . While Long considers phronesis , because of its plasticity in relation to different particular situations, suitable for the realm of education, he prefers sophia for philosophy of education (Long, , p. 143). It is clear that theorising in terms of sophia is much closer to Hirst's type of philosophy of education.…”
Section: Theoretical or Practical Philosophy: A Problem Or Pseudo‐promentioning
confidence: 99%
See 1 more Smart Citation
“…However, as Long has shown, theory had different meanings in Aristotle's view, the most comprehensive list of which includes techne , episteme, phronesis , noûs , and sophia . While Long considers phronesis , because of its plasticity in relation to different particular situations, suitable for the realm of education, he prefers sophia for philosophy of education (Long, , p. 143). It is clear that theorising in terms of sophia is much closer to Hirst's type of philosophy of education.…”
Section: Theoretical or Practical Philosophy: A Problem Or Pseudo‐promentioning
confidence: 99%
“…Answering this question, Paul Hirst and Wilfred Carr (Hirst and Carr, ) were involved in a debate which has itself been the subject of some discussion since then (e.g. Long, ; Misawa, ; Clark, ; MacAllister, ). This debate is in a sense a struggle between the two major European philosophical traditions, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…I therefore concur with Kristjánsson () who maintains that Wilfred Carr has (as one of the main proponents of what Kristjánsson dubs the ‘ phronesis‐praxis perspective’ of teaching ( PPP )) ‘recast and reconceived, rather than retrieved, Aristotelian ideas on a number of issues, so that the Aristotelian foundation, on which the PPP is supposed to build, has been changed beyond recognition’ (Kristjánsson, , p. 159). Long (), in a critique of the debate between Hirst and Carr similarly suggests that ‘a much more connected kind of theory is required than phronesis … for the philosophy of education’ (, p. 143). In this respect it will in the final section of this paper be suggested that Aristotelian thought might yet still offer a platform for a more ‘connected’ philosophy of education.…”
Section: The Philosophy Of Education and Aristotlementioning
confidence: 99%
“…Ever since Hirst's new-found emphasis on the educational significance of initiation into social practices the notion has been of interest to many (Long, 2008). In the work of John White general education is viewed as being concerned to promote 'a person in the round, a person with a life to lead, a path to follow through all its conflicts, opportunities, contingencies', as one 'who lives the life'.…”
Section: Pragmatism and Liberal Educationmentioning
confidence: 99%